Determination of Patulin By TLC From Mouldy Apples: Omar J. Al saree ;Khalid N., Jassim Thkra A. Hassen - Al saree, Omar J. (The Iraqi Journal of Veterinary Medicine, 2010)
Analysis of the decayed apples (van. Starking delicious), collected from the localmarket, for patulin mycotoxin, using column chromotography and TLC Plates showedthat the presence of the amount of patulin mycotoxin in the mouldy tissues (1.3 , 2.5 ,3.4 , 4.2, 5.5, and 6.4 ) cm in diameters were (5.1, 5.8, 6.3, 10.5, 12.3, and 14 ) μgpatulin/g moldy tissues respectively. According to this research also, Patulinmycotoxin could diffused to the surrounding mouldy tissues. It is found that (0.5and0.2), (1.0 and 0.5), and (1.5 and 0.5) μg patulin/g tissues in the first and secondcentimeters after mouldy tissues 4.2, 5.5 and 6.4 cm respectively, this phenomenondue to the presence of intracellular spaces in the tissues which allow to patulin todiffuse from mouldy to the healthy tissues there was no patulin found in the othersurrounding healthy tissues. Gram positive bacteria found to be more susceptible topatulin, the zone of inhibition against Staphyllococcus aureus was 10 to 11 mm indiameter at concentration 10 and 30 mg /ml respectively when compared with 0.3μg/ml streptomycin and 0.06 μg/ml ciprofloxacin while no inhibitory effect foundagainst Gram negative bacteria Klebsiella pneumoniae and Escherichia coli